Associations between folate metabolism biomarkers and cognitive impairment in older Chinese adults: a cross-sectional study - Lv, Huimin; Li, Jia; Chen, Lu; Lu, Keyi; Zhao, Xudong; Guo, Mengyuan; Lu, Hailong (Frontiers in Medicine, 2025)
BackgroundThe role of folate metabolism–related biomarker profiles in age-related cognitive impairment (ARCI) remains unclear. This cross-sectional study aimed to examine the association between folate metabolism-related biomarkers and cognitive performance in older Chinese adults.MethodsWe conducted a cross-sectional analysis of 100 participants aged between 56 and 87 years. Cognitive status was classified as ARCI if participants met the cutoff criteria on both the MMSE (<27) and MoCA (<26). Those meeting the cutoff criteria on both MMSE (≥27) and MoCA (≥26) were classified as cognitively normal (CN). Serum levels of folate metabolism-related biomarkers were compared between groups and analyzed for their associations with cognitive scores. Logistic regression was used to examine associations between individual biomarkers and cognitive impairment status. Multiple linear regression analyses were conducted to assess relationships with MMSE and MoCA scores, adjusting for age and education.ResultsCognitive impairment was prevalent among older adults at a rate of 56.3% (P < 0.05). The ARCI group showed significantly lower levels of vitamin B2 (VB2), folate (VB9) and lower MMSE and MoCA scores compared to the CN, while S-adenosylhomocysteine (SAH) and homocysteine (Hcy) levels were higher. MMSE and MoCA scores were positively correlated with serum VB2, VB9, and plasma S-adenosylmethionine (SAM) levels and negatively correlated with Hcy levels. Logistic regression showed that education and serum Hcy were significantly associated with cognitive impairment (AUC = 0.73). In addition to age, VB2, SAM and Hcy in the folate metabolic profile were significantly associated with MMSE and MoCA scores, accounting for 45.9 and 42.7% of the variance in these scores, respectively.ConclusionsVB2, SAM and Hcy may be associated with cognitive impairment in older Chinese adults and warrant further investigation as potential biomarkers.